Nerve excitability changes related to muscle weakness in chronic progressive external ophthalmoplegia. Issue 7 (July 2017) - Gueguen, Antoine; Jardel, Claude; Polivka, Marc; Tan, S. Veronica; Gray, Françoise; Vignal, Catherine; Lombès, Anne; Gout, Olivier; Bostock, Hugh
Highlights: Patients with chronic progressive external ophthalmoplegia due to large size deletions of mtDNA were studied. Nerve excitability abnormalities were found that correlated with skeletal muscle weakness. Abnormalities suggested a spread of mitochondrial dysfunction to Schwann cells. Abstract: Objective: To explore potential spreading to peripheral nerves of the mitochondrial dysfunction in chronic progressive external ophthalmoplegia (CPEO) by assessing axonal excitability. Methods: CPEO patients ( n  = 13) with large size deletion of mitochondrial DNA and matching healthy controls ( n  = 22) were included in a case-control study. Muscle strength was quantified using MRC sum-score and used to define two groups of patients: CPEO-weak and CPEO-normal (normal strength). Nerve excitability properties of median motor axons were assessed with the TROND protocol and changes interpreted with the aid of a model. Results: Alterations of nerve excitability strongly correlated with scores of muscle strength. CPEO-weak displayed abnormal nerve excitability compared to CPEO-normal and healthy controls, with increased superexcitability and responses to hyperpolarizing current. Modeling indicated that the CPEO-weak recordings were best explained by an increase in the 'Barrett-Barrett' conductance across the myelin sheath. Conclusion: CPEO patients with skeletal weakness presented sub-clinical nerve excitability changes, which were not consistent with axonal membrane depolarization, but suggested Schwann cell involvement. Significance: This study provides new insights into the spreading of large size deletion of mitochondrial DNA to Schwann cells in CPEO patients.